Ensuring Information Security within the Military Environmental Safety System (Моделювання, керування та інформаційні технології, 2025)
The growing complexity of military operations in environmentally hazardous zones has led to the increased reliance on digital technologies for radiation and chemical monitoring. Modern military environmental safety systems depend on distributed sensor networks, unmanned aerial vehicles (UAVs), automated data processing modules, and real-time telemetry to detect, assess, and respond to ecological threats. However, the integration of these digital components introduces new vectors of vulnerability, particularly in the domains of cyber and information security.This paper analyzes the crucial role of information security in maintaining the integrity, availability, and reliability of environmental monitoring data within military contexts. It outlines a comprehensive threat model that identifies common cyberattack scenarios such as data spoofing, signal interception, denial of service, and unauthorized access. To counter these risks, the article proposes a layered security architecture that incorporates encryption, authentication, anomaly detection, access control, and secure logging mechanisms. Each layer of the data lifecycle, from initial sensor acquisition to command-level decision support, is addressed in terms of its specific protection requirements and operational constraints.In addition to architectural design, a risk-based response matrix is introduced to guide the prioritization of protective measures based on threat probability and mission-criticality. The proposed framework is evaluated through scenario analysis and performance metrics, highlighting its potential to improve resilience and reduce system vulnerability in the face of both cyber and environmental threats.The study concludes that robust information security is not a peripheral function but a foundational element of effective environmental safety systems in modern armed forces. Its integration directly influences decision-making accuracy, troop protection, and mission continuity in complex operational theaters.